The Northernmost Confirmation of the Occurrence of Parrotfish (Sparisoma cretense Linnaeus, 1758) in the Eastern Mediterranean With Its First Record From Saros Bay (Northern Aegean Sea, Turkey) - Özgür Cengiz; Şenol Paruğ (Acta Natura et Scientia)
An ongoing warming trend is obviously proof in both the surface and deep waters of the Mediterranean Sea. The increasing seawater temperature renders this sea more receptive to invasion by thermophilic species and affects marine species and ecosystems. In this connection, a single specimen of Sparisoma cretense was caught on 20 September 2013 off the İbrice Bight at approximately 40°36’07.8”N 26°32’44.3”E (Saros Bay, Northern Aegean Sea, Turkey). This paper presents the first record of S. cretense in the Saros Bay (Northern Aegean Sea, Turkey), which is the northernmost confirmed occurrence of the parrotfish for the Eastern Mediterranean.